PENGARUH SOCIAL MEDIA MARKETING DAN BRAND EXPERIENCE TERHADAP PURCHASE DECISION KONSUMEN PADA PRODUK KOSMETIK DAN BRAND TRUST SEBAGAI MEDIATOR (Studi pada Konsumen Somethinc) - Lova, Tina Kurnia; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The growth of the cosmetic industry in Indonesia, which has increased in recent years, has made competition in this industry tighter, including local cosmetic brands. Companies have to find ways to improve their marketing and one of the strategies that can be used is social media marketing. The high use of social media by the public makes marketing through social media a powerful and low-cost strategy for companies to achieve their goals. Previous research stated that social media marketing had a positive and significant impact on purchasing decisions, but in fact, Somethinc, which is more active in conducting social media marketing, still ranked below Make Over as the most widely used local brand in Indonesia, according to Katadata (2022). The purpose of this study was to determine the effect of social media marketing and brand experience on purchasing decisions through brand trust as a mediating variable for Somethinc consumers in Indonesia. The sample used in this study amounted to 120 respondents who were selected by purposive sampling method and the data collection method used was distributing questionnaires online. The data that has been obtained is analyzed quantitatively by applying the Structural Equation Model (SEM) method with AMOS version 24 as a data processing tool. The results of the analysis in this study indicate that social media marketing has a positive and insignificant effect on purchasing decisions. The effect of social media marketing on purchasing decisions can be seen from the indirect effect through brand trust which is greater than the direct effect. Social media marketing and brand experience were found to have a positive and significant influence on brand trust, and brand trust is found to be positively and significantly related to purchasing decisions.